PENGELOLAAN DANA PENGEMBANGAN DAN PEMBERDAYAAN MASYARAKAT PT. VALE DALAM PEMBANGUNAN DI DESA GERESA KABUPATEN MOROWALI - Gumilang, Indra; Haris, Subhan; Labiro, Richard f (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Management of PT Vale Indonesia Tbk's Community Development and Empowerment (PPM) funds in Development in Geresa Village, East Bungku District, Morowali Regency. This research was carried out using qualitative descriptive with a descriptive research type. The types of data are primary data and secondary data, this study uses the theory put forward by George R. Terry and Leslie W. Rue (2019) 5 management indicators, namely planning, organizing, staffing, motivation, and supervision. The results of the study show that the management of PPM funds is still not optimal in planning, village deliberations have been carried out, but transparency and community involvement are still lacking in management. The main obstacles in implementation are the lack of active community participation and the lack of realization of the input proposed by the community. From the organizational aspect, the Activity Management Team (TPK) faces coordination constraints, time efficiency, as well as external factors such as weather and limited technology capabilities. The selection of the Activity Management Team (TPK) is carried out through village deliberations and determined by the Decree of the Village Head, but the challenge of transparency in fund management still exists. In terms of motivation, payment systems and incentives have been implemented, in supervision, monitoring is carried out by the village government and PT Vale, but community involvement in the audit is still low. Overall, the main challenges in managing PPM funds are transparency, community engagement, and program effectiveness. Improvements in planning, coordination, and supervision are needed so that PPM funds provide maximum benefits to the village community.